Nursing Mothers Knowledge, Attitude And Practice towards Breast Feeding - Junaid Zeb; Mukarram Mustajab; Muhammad Zeeshan; Sami Ullah; Shahila Qasim; Zeb Khalil (ziauddin University, 2018)
Objective: This study was conducted to explore breastfeeding practices and knowledge among postnatal mothers. Methods: Anobservational Cross-sectional study was carried out in the Neonatal Division, Department of Paediatrics and gynaecology at Mardan Medical Complex, Mardanfrom June 9 till September 30th, 2014.The data from 200 Nursing Mothers was collected using a structured Performa. In addition to demographic data, nursing mothers were questionedabout their knowledge and assessed about attitude towards breastfeeding. Questionnaire also included independent variables of the study. Data was analysed using SPSS version 21. Results: Out of total 200 children, 120(60%) were males while 80(40%) were females. Mothers who knew the importance of breast feeding were 178(89%), while 22(11%) didnot. Of total 116(58%)women added substitute for breast milk while 84(42%) didn't. who consider breastfeeding causes maternal weakness were 50 (25%) while 20(10%) didn't mentioned any reason, 20(10%) were employed while 180(90%) were not. Out of total the knowledge of the mothers with first baby was inadequate about initiation of breastfeeding of which 36% has no idea to breastfeed within 1/2 -1 hour after birth,44% have no idea about importance of colostrum feeding, 3% of mothers had problem in breastfeeding out of which 2% was because of sore nipple.The insufficient milk production was most common reason given by mothers for giving supplemental feed (65% cases). Conclusion: High scores were significantly correlated with high parity, better maternal education,higher maternal age,received antenatal care and higher socio economic status.